Buenas Prácticas Ambientales para el desarrollo del turismo, en el Parque Recreacional Yamburara, Parroquia Vilcabamba - Zuñiga Kirby, Jessy Ariel (2024)
This degree work has been called “Good Environmental Practices for the development of tourism in the Yamburara Recreational Park, Vilcabamba parish”, in response to the scarce application of correct environmental practices, therefore, the general objective states the following: Propose good environmental practices for the development of tourist activity in the Yamburara Recreational Park of the Vilcabamba Parish. Two specific objectives are derived from this section: First, carry out a diagnosis of good environmental practices of water, energy and solid waste resources within the park. Second, design a manual of good environmental practices for the development of tourism within the Yamburara Recreational Park. For the methodology, the quantitative-qualitative method was used with the support of consumption measurement tools and a performance evaluation matrix. In application of the methodology, the results of the environmental diagnosis yielded the following observations: 1) For water, it was found that it does not have a good drinking water supply and administration system. 2) For energy, the lack of renewable energy sources and saving elements was noted. 3) For solid waste, there is a lack of correct waste management and inefficient waste classification. From the observations presented, it is determined that they are the result of poor training of staff and consumers, lack of signage aimed at conservation and correct management of resources, and little information on water and waste control. Regarding the conclusions, it was determined that the park has a low performance in terms of the application of good environmental practices, so total intervention is needed, the manual of good environmental practices will allow the park to develop tourism in a way sustainable. As for the recommendations, they were directed to the park administrator so that the application of signage could be taken into account among other proposals raised in the manual.